2018
DOI: 10.2131/fts.5.123
|View full text |Cite
|
Sign up to set email alerts
|

The impact on the activity of acetylcholinesterase of a polylysine-ApoE peptide carrier targeting the blood brain barrier

Abstract: -The K16ApoE peptide has been demonstrated to deliver a supraphysiological level of protein therapeutics to the brain and further increase the life-span of mice with a lysosomal storage disorder (LSD). If successfully developed, K16ApoE would provide new treatments for LSD and many other neurological diseases. However, while the K16ApoE can cross the blood-brain barrier, data indicates a toxic response associated with it. The mechanism of toxicity must be resolved for further clinical translation. The toxic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…AChE is mainly distributed in nervous tissue and muscles (Wilson, 2014). Previous research (Michelena et al, 2018) hypothesized that K16ApoE inhibits AChE activity in the neuro-muscular junction and further leads to muscle spasms and respiration failure. The diaphragm is directly associated with respiration, and the brain can regulate respiration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AChE is mainly distributed in nervous tissue and muscles (Wilson, 2014). Previous research (Michelena et al, 2018) hypothesized that K16ApoE inhibits AChE activity in the neuro-muscular junction and further leads to muscle spasms and respiration failure. The diaphragm is directly associated with respiration, and the brain can regulate respiration.…”
Section: Discussionmentioning
confidence: 99%
“…The studies (Lu et al, 2018;Michelena et al, 2018) hypothesized that K16ApoE toxicity is induced by acetylcholinesterase (AChE) inhibition in the brain. From molecular docking, the authors found that K16ApoE…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…non-viral vector functionalised with a different ApoE-derived sequence (LRVRLASHLRKLRKRLLRDA) has been successfully used for the delivery of an array of both small drugs and proteins to the brain via intravenous (IV) injection [215][216][217][218]. However, the development of these P(Lys) 16 NPs has been hampered by a peptide dose-dependent toxicity associated to an unexpected inhibition of acetylcholinesterase, which still remains to be fully understood [219].…”
Section: Low-density Lipoprotein Receptorsmentioning
confidence: 99%
“…A previous study (Michelena et al, 2018) speculated that the toxicity of K16ApoE was caused by an acute reduction of acetylcholinesterase (AChE) activity at the neuromuscular junction. However, our previous work (Shao and Michelena, 2023) found that K16ApoE could not reduce AChE activity at lethal doses in animal experiments.…”
Section: Introductionmentioning
confidence: 99%